Office 365 core applications - Walsh, Heather; Safari eBooks ([Place of publication not identified] : CompuWorks, 2016)
This video is designed to introduce students to the core applications of Office 365.
Title from resource description page (viewed August 29, 2016).
Presenter, Heather Walsh.
Keywords: Microsoft Office; Integrated software; Electronic books